Bruxismo y su influencia en el desarrollo de alteraciones a nivel de cavidad oral. - Martínez Loma, Jessica Mishell (2024)
Introduction: bruxism is one of the most common oral diseases, because its etiology is multifactorial, stress and psychological factors would be one of its main causes, this disorder can cause morphological changes in the masticatory system that negatively impact oral health. Materials: classification and organization tools were used. Search methods were used in different scientific databases such as PubMed, Elsevier, Scielo and Google Scholar, choosing articles according to quality and relevance criteria. A total of 80 relevant articles were identified and analyzed to obtain significant conclusions. Methodology: The bibliographic research on bruxism and its influence on the development of oral cavity alterations was descriptive, cross-sectional and qualitative. Results: Bruxism is a non-functional habit and of variable ethology, there are different related factors, among the main factors we have: peripheral and central factors. This is why bruxism, if not diagnosed correctly and in time, can cause multiple consequences in the oral cavity, especially at the dental, muscular and articular levels. Discussion: A variety of oral conditions related to bruxism were demonstrated, including dental wear, dental sensitivity, dental mobility and temporomandibular disorders.